The Role of Store Layout and Visual Merchandising in Food Retailing (European Journal of Marketing and Economics, 2025)
Literature proposes a number of store attributes as potentially significant factors affecting customers’ evaluation of retailer’s image, store loyalty and overall satisfaction, such as merchandise assortment and quality, service in general, personnel, store layout, convenience, cleanliness and atmosphere. Successful and profitable retailers use effectively each and every square meter of the retail space, both in the store and in the warehouse. Since retail space is costly, space management is gaining strategic importance in retailing. Appropriate store floor plans, location of certain merchandise categories, levels of inventory and visual displays are crucial factors of proper use of retail space. Misuse of retail space can be detrimental to retailer’s bottom line as it can result in difficulties in orientation of customers in the store, their shorter stay in the store, consequentially lower sales and possible loss of customers. It is hypothesised that effects of poor space management are even more pronounced in retail formats that incorporate self-service as a selling method with food retailers being especially at risk because in a setting where consumers can find identical merchandise in more than one store, layout and presentation become key differentiating factors. An empirical study is conducted as to determine the role of food store layout and visual merchandising compared to other store attributes in achieving customer satisfaction and to define preferable large food store layout among consumers. Research results imply that retailers need to create stimulating atmosphere and appealing layout in order to trigger consumer's buying decision.
Keywords: store layout, visual merchandising, retail space management, food retailing.